(untitled) (International Journal of Engineering and Computer Science, 2013)
This paper proposes Data and Process Management to facilitate the Teamwork in a collaborative product Development with internet and intranet support system environment. Nowadays very high competition in Global marketing with global & local customers. So, we need to increase the Manufacturing process globally. To implement these processes will require integrating people, process, machine and computers. The total development is meant for customer satisfaction as per customer specifications. PDM PORTAL is an integrated, information approach to all aspects of product, from customer’s, manufacturing deployment and maintenance with finished product.PDM PORTAL suites enable accessing, updating, manipulating and reasoning about customer, process and product Globally-Locally. This integration takes place through well accepted human and electronics protocols. So, try to introduce the new concept to integrate PDM, ERP, CRM and SCM (Product Data management, Enterprise resource planning, Customer relations management, and Supply chain management – product, processes, customer and Web Protocol Development. For this integration time to be reduced to develop the product and time to market as per customer satisfaction and this trend expected in next generation. The Data and Product Process to get and Distributed geographically. PECS implementation in enterprises is aimed at delivering products faster making Product development process more systematic as per customer requirements. PECS system includes storage , Inventory, processing of Design information and manufacturing Data in an engineering organization with Product Centric approach. We develop architecture for Product Master Data [PMD] that includes CAD/CAM/CAE of Design and Manufacturing Process of Automobile Industry. Therefore we suggest through this support can access all design and manufacturing information in the enterprise must be Web-based because of its universal Data efficiently using with distributed Data. Using this scenarios and systems we will show effectively using PECS Tool support geographically access for Time to Market.